Entrenchment and productivity: The role of input in the code-mixing of a German-English bilingual child - Quick, Antje Endesfelder; Hartmann, Stefan; Backus, Ad; Lieven, Elena (Applied Linguistics Review, 2021)
This paper investigates the role of input in the code-mixing (CM) of a German-English bilingual child between the age of 2;3 until 3;11. Supporting a usage-based approach to linguistic theory, multiword units are shown to play an important role in language acquisition scenarios, both in the input children receive as well as in their own early language production. The current study combines findings from Child-directed-speech (CDS) and children's output to investigate whether utterance-initial, multiword units in the code-mixing of a German-English bilingual child can be traced back to patterns found in the input. The findings reveal that a large proportion of the child code-mixed (78%) and parental input (59%) data instantiate the selection of multiword units. Additionally, we found that many of the units used by the child (74%) correlate with units in the parental input suggesting that bilingual children construct their code-mixed utterances on the basis of both concrete lexical strings and partially schematic patterns they have heard before.
CRIS-Team Scopus Importer:2022-11-17
Keywords: code-mixing; multiword units; role of input; traceback; usage-based approach